Mode-locked erbium-doped fiber laser employing cobalt doped zinc oxide saturable absorber - Babar, Ibrahim M.; Ahmed, Mahmoud Hazzaa M.; Harun, Sulaiman Wadi; Yasin, Moh (Old City Publishing, 2018)
We demonstrated a passive mode-locked Erbium-doped fiber laser (EDFL) based on cobalt-doped zinc oxide (Co-ZnO) nanorods saturable absorber (SA). The nanorods were embedded into a polyvinyl alcohol (PVA) film as a passive mode-locker. The SA was fabricated by mixing nanorods Co-ZnO solution with PVA solution and dried it in a room temperature. The thin film was sandwiched between two fiber ferrules and incorporated into an Erbium-doped fiber laser (EDFL) cavity operating in anomalous fiber dispersion of -4.571 ps 2 to generate a mode-locking pulses train. A stable self-started soliton pulses train was generated at threshold pump power of 219 mW. The central wavelength and repetition rate of the laser were 1559.5 nm and 1.007 MHz, respectively. The pulse width and maximum pulse energy obtained are 462.8 ns and 5.1 nJ, respectively at a pump power of 248 mW. The Co-ZnO nanorods film was fabricated by a simple processing technique, and it has a modulation depth of 6 % and saturating intensity of 60 MW/cm 2.